PP18 Ambulance attendance at diabetes or diabetes-related emergencies in care homes – cross sectional database study. Issue 10 (24th September 2019) - Niroshan Siriwardena, A; Law, Graham; Smith, Murray D; Iqbal, Mohammad; Phung, Viet-Hai; Spaight, Anne; Brewster, Amanda; Mountain, Pauline; Spurr, Keith; Ray, Mo; Idris, Iskandar; Khunti, Kamlesh
Abstract : Background: Diabetes, which affects over 1 in 5 nursing or care home residents, may lead to diabetes-related emergencies with ambulance call-outs and hospitalisation. Our aim was to investigate the epidemiology of diabetes-related emergencies in care home residents which involved an ambulance attendance. Methods: We used a cross-sectional design to investigate emergency ambulance attendances to people in nursing and residential care homes presenting with diabetes-related emergencies across the East Midlands between January 2012 and December 2017. We used clinical and dispatch data from East Midlands Ambulance Service NHS Trust (EMAS) and care home data from the Care Quality Commission, including call category, timing, location, place of residence, clinical or physiological status, treatments, outcome (conveyance) and costs in the analysis. Results: Overall 219722 (6.7% of 3.3 million) attendances were to care home residents of which 12080 were for diabetes-related emergencies. Of 3152 care home patients categorised as having a 'diabetic problem' 1, 957 (62.1%) were conveyed to hospital. This was not significantly different to the rate for other patients, taking into account other factors, despite access to trained staff in care homes. Statistically significant factors associated with conveyance included reduced consciousness level (OR 0.91, 95% CI 0.87–0.95), elevated heart (1.01, 1.01–1.02) or respiratory rate (1.08, 1.06–1.10), no treatment for hypoglycaemia (0.54, 0.34–0.86) or additional co-morbid medical (but not psychiatric) problems. Cost to EMAS was significantly lower when a patient was conveyed, by some £18 (95% CI £11.94–£24.12), but this would not outweigh downstream NHS costs arising from hospital care. For the simulation in which all trusts mean NHS Reference Costs were used, conveyance was no longer significant in the cost model. Conclusion: Conveyance to hospital was common for care home patients with diabetes-related emergencies and more likely when conscious level was impaired, certain physiological measures abnormal or treatment for hypoglycaemia was not given.